2020
DOI: 10.3390/cancers12061451
|View full text |Cite
|
Sign up to set email alerts
|

RKIP Regulates Differentiation-Related Features in Melanocytic Cells

Abstract: Raf Kinase Inhibitor Protein (RKIP) has been extensively reported as an inhibitor of key signaling pathways involved in the aggressive tumor phenotype and shows decreased expression in several types of cancers. However, little is known about RKIP in melanoma or regarding its function in normal cells. We examined the role of RKIP in both primary melanocytes and malignant melanoma cells and evaluated its diagnostic and prognostic value. IHC analysis revealed a significantly higher expression of RKIP in nevi comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 68 publications
1
11
0
Order By: Relevance
“…To this end, we interrogated public databases for correlations between the expression of MGRN1 and relevant clinical parameters and we also used a collection of melanoma specimens previously obtained at the Biocruces Bizkaia Health Research Institute (BBHRI). This sample cohort has been described and successfully used in previous studies [ 28 , 33 ], and the relevant clinical information on the patients is available. Using the data compiled in the GEPIA database ( ), we compared the relative expression of the MGRN1 gene in different types of tumors from human patients and paired normal tissues (TCGA and GTEx cohorts), as well as in melanoma compared with normal skin.…”
Section: Resultsmentioning
confidence: 99%
“…To this end, we interrogated public databases for correlations between the expression of MGRN1 and relevant clinical parameters and we also used a collection of melanoma specimens previously obtained at the Biocruces Bizkaia Health Research Institute (BBHRI). This sample cohort has been described and successfully used in previous studies [ 28 , 33 ], and the relevant clinical information on the patients is available. Using the data compiled in the GEPIA database ( ), we compared the relative expression of the MGRN1 gene in different types of tumors from human patients and paired normal tissues (TCGA and GTEx cohorts), as well as in melanoma compared with normal skin.…”
Section: Resultsmentioning
confidence: 99%
“…Primary lesions of early-stage malignant melanoma show an overall decrease of RKIP when compared with benign lesions (i.e., nevi) [ 68 ]. As RKIP downregulation alters cellular processes closely related to the neoplastic transformation such as proliferation and migration it might be a useful marker for early diagnosis rather than prognosis.…”
Section: Rkip and Cancermentioning
confidence: 99%
“…Furthermore, post-translational regulation of RKIP in melanoma involves mir-21, one of the targets of NANOG and EMT. Some evidence suggests a direct correlation between mir-21 and RKIP levels as overexpression of RKIP in primary melanoma cultures is associated with a significant reduction of mir-21 and at the same time with lower cell mobility [ 68 ].…”
Section: Rkip and Cancermentioning
confidence: 99%
“…In this context, for many years we have focused on classifying early-stage melanoma patients on the basis of serological and novel histopathological biomarkers that can be assessed at the time of melanoma diagnosis and initial surgery, thereby identifying profiles that are most likely to develop to more advanced stages and enabling more effective treatments for metastatic disease to be implemented [ 9 , 10 , 11 ]. Thus, in independent studies we previously studied, on the one hand, cytokines in the serum of patients [ 9 ] and, on the other hand, histopathological biomarkers in melanoma biopsies [ 9 , 10 ]. We found that cytokines such as IL-4, IL-6, and GM-CSF are significantly related to a bad prognosis of patients [ 9 ].…”
Section: Introductionmentioning
confidence: 99%